Ketogenic diet for patients with type II diabetes mellitus (Research, Society and Development, 2020)
Type II diabetes mellitus in the 21st century is one of the biggest public health problems, which affects a large part of the population and is the most prevalent form in the world, corresponding to about 90% of all cases of diabetes, dysfunction of a growing epidemic of developed and developing parents. It was observed that its cause is mainly related to obesity problems and that weight loss favors treatment. Thus, the inclusion of a diet and the change in lifestyle can contribute positively to an improvement in patients with this disease. From this, the present study aimed to carry out an integrative review on the influence of the ketogenic diet as an aid in the treatment of type II diabetes mellitus and to understand such management that can contribute to the diabetic individual. It is an integrative review, being used as a method of data collection, with research in the period published in the databases: Scielo, Pubmed, Capes and relevant body in the area. Articles from 2011 to October 2019 were selected in Spanish and English Portuguese found in abstracts and full texts. Through this study it was concluded that the ketogenic diet has a reduction in body mass, helps to reduce insulin resistance, improves plasma glucose levels and consequently contributes to the reduction of type II diabetes mellitus.